Picture Animation in Visual Art Classes: Making an Animation Movie Project with 8th level Students from S. Jorge Island – Azores - Fernandes, Paulo Oliveira (2015)
The present report intends to give an account of a pedagogical practice conducted within Visual Arts, which explores the potential of the animation within the classroom context. The work has been developed at the Escola Básica e Secundária de Velas, S. Jorge island, Azores, during the 2013/2014 school year and it lead to the creation of three animation movies inspired by local legends. The pedagogical practice currently being mentioned has been developed on a formal learning context and it fits theeducational potential of animation, the project-oriented working methodologies and the program guideline of the Visual Arts curriculum. The Project named “Lendas de S. Jorge” is a pedagogical work, conducted by the teacher and the students, that uses the local imaginary and cultural heritage in order to achieve the curricular learning, by significant learning methods.